2021
DOI: 10.3390/cells10112843
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Endothelial Barrier Function in the Inflammatory Setting: Indication for a Cytokine-Mediated Post-Transcriptional Mechanism by Virtue of Upregulation of miRNAs miR-29a-3p, miR-29b-3p, and miR-155-5p

Abstract: Dysfunction of the endothelial barrier plays a central role in the pathogenesis of both acute and chronic inflammatory processes such as sepsis or atherosclerosis. Due to attenuation of endothelial cell contacts, there is an increased transfer of blood proteins and fluid into the surrounding tissue, which relates to edema formation and distribution disorders. However, the mechanisms underlying these responses are not fully understood. In this study, we used human endothelial cells to mimic the loss of barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous research has showed that a reduction in claudin-1 expression leads to the appearance of neuropathic pain symptoms in animal models [ 103 ] and some evidence suggest that this is the same in humans [ 104 ]. Interestingly, miR-155-5p directly targets and suppresses claudin-1 and in the present review an upregulation of miR-155-5p across five studies was present; this could suggest that the long-term neuropathic pain-like symptoms present in long COVID could be due to a suppression of claudin-1 and a subsequent increase in endothelial permeability [ 79 ]. Furthermore, an indirect modulation of claudin-1 in long COVID can also be hypothesized; by means of the modulation of matrix metalloprotease-9 (MMP-9), an important regulator of axon demyelination and extension [ 105 ]; MMPs are predominantly expressed in Schwann cells of peripheral nerves under normal conditions and are upregulated in peripheral nerve injury [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous research has showed that a reduction in claudin-1 expression leads to the appearance of neuropathic pain symptoms in animal models [ 103 ] and some evidence suggest that this is the same in humans [ 104 ]. Interestingly, miR-155-5p directly targets and suppresses claudin-1 and in the present review an upregulation of miR-155-5p across five studies was present; this could suggest that the long-term neuropathic pain-like symptoms present in long COVID could be due to a suppression of claudin-1 and a subsequent increase in endothelial permeability [ 79 ]. Furthermore, an indirect modulation of claudin-1 in long COVID can also be hypothesized; by means of the modulation of matrix metalloprotease-9 (MMP-9), an important regulator of axon demyelination and extension [ 105 ]; MMPs are predominantly expressed in Schwann cells of peripheral nerves under normal conditions and are upregulated in peripheral nerve injury [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 86%
“…Mc Donald et al [ 78 ] found that miR-155-5p was downregulated in COVID-19-positive nasopharyngeal swabs. However, an upregulation of this miRNA has been linked to several disease states, mainly linked to inflammation [ 79 ]. The upregulation found by Keikha et al [ 60 ] in serum samples of critical COVID-19 cases, plus the negative correlation with its target SOCS1, shows the role of miR-155-5p in promoting neuronal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…When exposed to the proinflammatory cytokines IL-1b, TNF-a, and IFN-g, it could lead to local breaks at endothelial cell-cell junctions and exacerbated endothelial barrier dysfunction during the inflammatory response (62). Maucher et al (63) demonstrated significant changes in the miRNA expression profile of endothelial cells in response to the stimulation by inflammatory cytokines, which may be involved in endothelial permeability regulation. Among them, miR-29a-3p, miR-29b-3p and miR-155-5p expression was significantly increased and suppressed the adhesion protein expression in endothelial cells after transcription.…”
Section: Modulation Of the Inflammatory Responsementioning
confidence: 99%
“…A significant downregulation of miR-29a in PCOS patients was associated with an increased antral follicle count and decreased aromatase expression and estradiol production in GCs. However, miR-29a downregulation may exert both anti-inflammatory and proinflammatory effects, as was demonstrated in endothelial and hepatic cells, respectively [ 220 , 221 ].…”
Section: Epigenetic Modulation Of Androgenic Activity In Response To ...mentioning
confidence: 99%